2016
DOI: 10.1152/jn.00629.2016
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis selectively shapes the presynaptic action potential waveform

Abstract: Mitochondria are major suppliers of cellular energy in neurons; however, utilization of energy from glycolysis vs. mitochondrial oxidative phosphorylation (OxPhos) in the presynaptic compartment during neurotransmission is largely unknown. Using presynaptic and postsynaptic recordings from the mouse calyx of Held, we examined the effect of acute selective pharmacological inhibition of glycolysis or mitochondrial OxPhos on multiple mechanisms regulating presynaptic function. Inhibition of glycolysis via glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 90 publications
10
72
1
Order By: Relevance
“…For instance, Sada et al showed that inhibition of LDH resulted in a 70% reduction in excitatory postsynaptic currents, most likely due to a decrease in synaptic transmitter release (as the postsynaptic target cells were recorded in whole‐cell configuration with 4 mM ATP in the intracellular solution, preventing any energy shortage from LDH blockade). Presynaptic machinery presumably relies mostly on glycolysis‐provided ATP (Lujan et al, ), and therefore the reported LDH effect was most likely underlain by presynaptic glycolysis inhibition. Thus, similar to the acute effects of 2‐DG, the initial decrease in network activity induced by energy deprivation can cause a short‐term antiseizure effect, although an opposite proseizure effect cannot be excluded (see Gasior et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sada et al showed that inhibition of LDH resulted in a 70% reduction in excitatory postsynaptic currents, most likely due to a decrease in synaptic transmitter release (as the postsynaptic target cells were recorded in whole‐cell configuration with 4 mM ATP in the intracellular solution, preventing any energy shortage from LDH blockade). Presynaptic machinery presumably relies mostly on glycolysis‐provided ATP (Lujan et al, ), and therefore the reported LDH effect was most likely underlain by presynaptic glycolysis inhibition. Thus, similar to the acute effects of 2‐DG, the initial decrease in network activity induced by energy deprivation can cause a short‐term antiseizure effect, although an opposite proseizure effect cannot be excluded (see Gasior et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adeno‐associated virus encoding the GECI GCaMP6m (T. W. Chen et al, ) was procured from the Penn Vector Core in the Gene Therapy Program of the University of Pennsylvania (#AV‐1‐PV2823, 1.78 × 10 13 GC/mL, in sterile PBS). This virus was injected into the ventral cochlear nucleus of neonatal (P1) mice, using procedures previously described (Chen, Cooper, Kalla, Varoqueaux, & Young, ; Lujan, Kushmerick, Das Banerjee, Dagda, & Renden, ; Pilpel, Landeck, Klugmann, Seeburg, & Schwarz, ). Briefly, mice were anesthetized via hypothermia on ice for 5 min until unresponsive, then fixed on a stereotaxic surgery platform.…”
Section: Methodsmentioning
confidence: 99%
“…Transverse brainstem slices containing the medial nucleus of the trapezoid body (MNTB) were cut at 200 µm using a vibratome (VT 1200S, Leica Microsystems, Germany), as previously described (Lujan et al, ; Singh, Miura, & Renden, ). The slicing solution contained (in mM): 85 NaCl, 2.5 KCl, 25 glucose, 25 NaHCO 3 , 1.25 NaH 2 PO 4 , 75 sucrose, 0.5 CaCl 2 , 7 MgCl 2 , 3 myo‐inositol, 2 Na‐pyruvate, and 0.4 ascorbic acid; the pH was 7.4 when continuously bubbled with carbogen gas (95% O 2 –5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cox, Bachelard, and colleagues (see references cited above), Okada and Lipton (), and, more recently, Ivanov et al () concluded that glycolysis plays a key role in neuronal activity in brain slices, as observed by Bak and colleagues () in cultured neurons. Examples of preferred functions for glycolysis in neurons include vesicular glutamate loading (Ikemoto et al, ; Ueda and Ikemoto, ), calcium clearance (Ivannikov et al, ), and presynaptic action potential waveform (Lujan et al, ).…”
Section: Lactate and The Cellular Basis Of Brain Energy Metabolism Dumentioning
confidence: 99%